THE IMPACT OF ABORTIONS ON THE HEALTH OF THE MULTIPAROUS PREGNANT WOMEN WITH IRON DEFICIENCY ANEMIA - Aliyeva, P.I. (World of Medicine and Biology, 2023)
Among the multiparous women, abortions were quite common and were accompanied by complications in the clinic during the subsequent pregnancy. The research aimed at the analysis of the course of pregnancy and childbirth in multiparous women with iron-deficiency anemia with a history of induced and spontaneous abortion. The course of pregnancy and childbirth was investigated in 80 pregnant women with iron deficiency anemia, aged 28-36. The research was conducted on women of reproductive age including 25 multiparous women without a history of abortion and 55 multiparous women with history of abortion. The obtained results were analyzed by discriminant and variance analysis methods. The risk of miscarriage was in 24.0% of women without a history of abortion, and in 54.5% of women with a history of abortion (Pχ2=0.011; PU =0.011), and early leaking of amniotic fluid was in 44.0% of women without a history of abortion, and in 54.5% of women with a history of abortion (Pχ2=0.382; PU=0.385). The risk of miscarriage was found in 7 (30.4%) multiparous women with mild anemia without a history of abortion, and 16 (69.6%) multiparous women with a history of abortion; in 17 multiparous women with moderate anemia without a history of abortion (31.5%), and 37 (68.5%) multiparous women with a history of abortion; 1 multiparous woman with severe anemia without a history of abortion (33.3%), and in 2 (66.7%) multiparous women with a history of abortion Pχ2=0.993. The number of abortions in the anamnesis of multiparous women with IDA is high. Carrying out propaganda and promotion work in women’s counseling centers can prevent both unintended pregnancies and complications of pregnancy and childbirth.